Analisis penyusunan laporan keuangan Badan Usaha Milik Desa “Satu Hati” berdasarkan Keputusan Menteri Desa PDTT No 136 Tahun 2022 (Studi kasus Desa Linelean Kecamatan Modoinding) - Kapahang, Raisha Jibrilia; Kalangi , Lintje; Pinatik, Sherly (Yayasan Widyantara Nawasena Raharja, 2025)
Village-Owned Enterprises (BUMDes) are village business institutions managed by the community and village government to develop the village economy. They are established based on the needs and potential of the village. BUMDes were founded as an initiative to improve the economy and welfare of village communities. The Decree of the Minister of Villages, Development of Disadvantaged Regions, and Transmigration No. 136 of 2022 on the Preparation of BUMDes Financial Reports aims to ensure orderly administration, transparency, accountability, efficiency, and effectiveness in the financial management of Village-Owned Enterprises. This research aims to conduct an in-depth analysis of the preparation of financial reports for Satu Hati Village-Owned Enterprises based on the Ministerial Decree PDTT No. 136 of 2022. The research employs a descriptive qualitative method, which is used to collect, analyze, and describe data related to the preparation of BUMDes financial reports. The resource persons in this study include the Village Head, Chairman of BUMDes, Secretary of BUMDes, and Village Assistant. The research findings indicate that the financial reports of BUMDes Satu Hati are not fully aligned with the PDTT Village Ministerial Decree No. 136 of 2022 due to various factors, including internal and external obstacles and challenges.